(untitled) (Revista Electrónica Calidad en la Educación Superior, 2025)
The article examines the relationship between career adaptability and job success among graduates of the Universidad LCI Veritas during the 2017-2022 period based on their career trajectories. A quantitative approach was used, with a non-experimental, transactional design and a correlational scope. A survey was administered to a sample of 250 individuals, which was probabilistic and stratified by career. The main finding was a significant and positive correlation between the two variables [r=0.455, n=250, p<0.000], thus accepting the working hypothesis. The conclusion is that the ability to adapt to changes increases job success opportunities, particularly in terms of career development, and vice versa.